OVERVIEW OF MALARIA SURVEILLANCE IN THE ELIMINATION PHASE AT THE OESAPA COMMUNITY HEALTH CENTER - Wahyuni , Maria Magdalena Dwi; Landi, Soleman; Pare, Maria Saveryani Dua; Sabet, Kristina Novaeli; Dubu, Yansenin; Manu, Nadia Margarita (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2026)
Malaria remains a significant public health challenge, particularly in regions that have achieved elimination but remain vulnerable to imported cases due to high population mobility. This study describes the malaria surveillance system at the Oesapa Community Health Center during the elimination phase, specifically assessing its readiness to detect, report, and respond to cases in a timely. Employing a qualitative descriptive design, the study involved five key informants through in-depth interviews and document reviews, followed by a narrative analysis of planning, implementation, monitoring, and evaluation. The results indicate that all surveillance stages align with national guidelines, including data-driven planning, early detection via laboratory testing, travel history recording, and routine reporting. While the system at Oesapa is categorized as 'good,' enhancements in human resource capacity, migration surveillance, and cross-sector coordination are essential to prevent malaria reintroduction and sustain elimination status.